Implementation of the Monopoly Media-Assisted PBL Model to Improve Motivation and Learning Achievement in Pancasila Education - Septiani, Lina; Muslim, Aji Heru (Jurnal Gentala Pendidikan Dasar, 2026)
This study addresses the deficiencies in Pancasila Education learning outcomes and motivation among fifth graders at SD N 1 Susukan. Initial data indicated that student scores fell short of the Learning Objective Achievement Criteria (KKTP) due to conventional teaching models, unengaging media, and low classroom participation. To tackle this, the research investigates the deployment of a Problem-Based Learning (PBL) model coupled with monopoly game media. Conducted as a two-cycle Classroom Action Research (CAR), this study utilizes a mixed qualitative-quantitative descriptive approach. Data were harvested from 28 fifth-grade students via observation, motivational questionnaires, achievement tests, and documentation, then evaluated using descriptive statistics and qualitative techniques. The intervention proved highly effective; student motivation climbed from 71% (Cycle I) to 85% (Cycle II), and achievement proficiency rose from 62.50% to 82.14%. Ultimately, the combination of PBL and monopoly media significantly bolsters fifth-grade student achievement and motivation in Pancasila Education.